2013
DOI: 10.1021/jm3011349
|View full text |Cite
|
Sign up to set email alerts
|

Core Refinement toward Permeable β-Secretase (BACE-1) Inhibitors with Low hERG Activity

Abstract: By use of iterative design aided by predictive models for target affinity, brain permeability, and hERG activity, novel and diverse compounds based on cyclic amidine and guanidine cores were synthesized with the goal of finding BACE-1 inhibitors as a treatment for Alzheimer's disease. Since synthesis feasibility had low priority in the design of the cores, an extensive synthesis effort was needed to make the relevant compounds. Syntheses of these compounds are reported, together with physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 62 publications
3
56
0
Order By: Relevance
“…Our computational calculations, performed at the molecular level of two amino‐2 H ‐imidazoles, revealed that the core is the largest fragment responsible for the inhibitory activity, supporting the conclusion of Ginman et al, who suggested that the core is the region that needs to be early optimized in the lead generation phase to define a framework for future modifications . The activity difference between these two compounds is mainly due to the different contribution of the R 2 group to the binding affinity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our computational calculations, performed at the molecular level of two amino‐2 H ‐imidazoles, revealed that the core is the largest fragment responsible for the inhibitory activity, supporting the conclusion of Ginman et al, who suggested that the core is the region that needs to be early optimized in the lead generation phase to define a framework for future modifications . The activity difference between these two compounds is mainly due to the different contribution of the R 2 group to the binding affinity.…”
Section: Discussionsupporting
confidence: 85%
“…However, it should be considered that the remaining hydrophobic interactions must complement the hydrogen bond in a cooperative way. In fact, groups like R 2 of compound (S) ‐1m, capable of hydrogen bonding with Trp76 (along with the cooperation of multiple hydrophobic interactions) have been previously used in the design of new and potent inhibitors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,33,35 All of the selected core structures were synthesized with wellcharacterized substituents from previous in-house series. 1 There were four reasons for immediately converting the core fragments into full-sized test compounds: (1) With a molecular weight above 300, we wanted to avoid a seemingly high permeability only due to a low molecular weight. 28,29 (2) By testing larger molecules, with, e.g., higher target activity compared to fragments, we wanted to enter a reliable detection range in the in vitro assays.…”
mentioning
confidence: 99%
“…Herein we report a new transition-metal-catalyzed MCC which uses epoxides, imines, and CO as building blocks to construct 1,3-oxazinan-4-ones (1). This heterocycle is useful as a key intermediate in the total synthesis of natural products, [19] or as a precursor for the synthesis of b-hydroxy acids, [20] b-hydroxy esters, [21] b-hydroxy amides, [22] a,b-epoxycarboxylic acids, [23] and 1,3-amino alcohol derivatives, [24] all of which are valuable synthetic intermediates for the synthesis of pharmaceutically important compounds. To date there are only two major synthetic routes to such heterocycles, including acid-catalyzed dehydration-condensation of various aldehydes or ketones with appropriate hydroxy amides, [25] and hetero-Diels-Alder cycloadditions between aldehydes and 2aza-3-silyloxy-1,3-butadienes.…”
mentioning
confidence: 99%